Reconstruction of a Large Groin Defect using Pedicled Chimeric Tensor Fascia Lata and Vastus Lateralis Muscle Flaps Following Malignant Melanoma Excision: A Case Report - Archita N Rai; Swati Deshpande; Firoz Borle; Raju Shinde; Aditya Kale (Journal of Clinical and Diagnostic Research)
The reconstruction of large oncologic defects, especially in the groin region, poses significant surgical challenges due to the exposure of vital structures such as the femoral vessels. A 68-year-old male, previously treated for melanoma of the left foot, presented with a recurrent swelling in the left inguinal region. Fine Needle Aspiration Cytology (FNAC) confirmed malignant melanoma. Imaging studies revealed a lobulated, infiltrative lesion in the left proximal thigh, abutting the femoral triangle but without muscle invasion. The patient underwent radical excision of the lesion along with inguinal lymph node dissection, resulting in a 20×10 cm defect with exposed femoral vessels that required complex reconstruction. A pedicled chimeric left Tensor Fascia Lata (TFL) perforator flap and a vastus lateralis muscle flap were harvested. The TFL flap was raised based on a single dominant perforator, while the vastus lateralis muscle flap was based on the descending branch of the Lateral Circumflex Femoral Artery (LCFA). Both flaps were successfully tunneled under the rectus femoris muscle and inset into the defect. The donor site was partially closed, and the remaining area was planned for delayed secondary skin grafting. The pedicled chimeric TFL and vastus lateralis flaps effectively covered an extensive groin defect with exposed femoral vessels. This approach offers a robust reconstructive option for complex oncologic defects, ensuring functional and aesthetic outcomes. Further studies and case series are warranted to explore the versatility and limitations of this technique.